TRACE FOSSILS FROM THE UPPER CRETACEOUS CAPACETE FORMATION, SANFRANCISCANA BASIN, CENTRAL BRAZIL - Sedorko, Daniel; Alessandretti, Luciano; Warren, Lucas Verissimo [UNESP]; Verde, Mariano; Rangel, Caio Cesar; Ramos, Kimberly Silva; Netto, Renata Guimaraes (Polish Geological Soc, 2020)
The Upper Cretaceous Capacete Formation, from the intracratonic Sanfranciscana Basin, central Brazil, consists of epiclastic sediments with a significant aeolian contribution. This unit has been traditionally interpreted as deposited by alluvial fans distally grading to braided rivers in an arid- to semiarid climate within the central part of southwestern Gondwana. Locally, some expositions with wide lateral extension show architectural elements indicative of deposition in meandering rivers, such as floodplain fines (FF) interbedded with crevasse splay (CR), lateral-accretion macroforms (LA), and channels (CH). Bioturbation within the meandering fluvial deposits is commonly associated with the floodplain element, mainly occurring in fine-grained sandstone and mudstone. The lateral-accretion elements and channel deposits are barren of trace fossils. Sandstone with climbing ripples (Sr) from the element CR show low bioturbation of meniscate trace fossils assigned to Taenidium, Beaconites, and Scoyenia ichnogenera. Simple vertical and horizontal burrows identified as Skolithos and Palaeophycus occur associated with Taenidium and Camborygma in sandstone facies (Sr, St and Sh), as well as rhizoliths, representing the Scoyenia ichnofacies. The predominance of trace fossils related to the FF and CR architectural elements attests to the colonization mostly by insects in episodic and vegetated flood plains of the meandering river system from the Capacete Formation. Thus, despite the primarily arid to semiarid conditions interpreted for the inner parts of the newly formed South American continent during the Upper Cretaceous, our new data support deposition under humid conditions in some intervals of the Capacete Formation from the Sanfranciscana Basin.
Keywords: Meandering fluvial system; insects; continental trace fossils; Scoyenia ichnofacies